Climate change, ecosystems and smallholder agriculture in Central America: an introduction to the special issue - Imbach, Pablo (2017)
Central America is one of the regions most exposed to climate change (Giorgi 2006). A narrow isthmus between the Pacific Ocean and the Caribbean Sea, it is strongly affected by droughts, hurricanes and the El Niño-southern oscillation (ENSO) phenomena (CEPAL 2011). As a result, three countries in the region rank in the top 10 of the Global Climate Risk Index (Kreft and Eckstien 2013) based on the impacts of extreme weather events between 1993 and 2012.Much of the regional economy is based on agriculture. In Guatemala, Honduras and Nicaragua, more than two thirds of the population depends on agriculture. This agricultural base is often intimately tied to ecosystems, especially in diverse farming systems of smallholders. But it is increasingly threatened by climate variability and change (Bouroncle et al. 2016; Baca et al. 2014), which are inducing changes in areas suitable for crops and leading to high yield variability. Storms, floods and droughts have had the greatest impacts on agriculture in Central America over the last century (Guha-Sapir et al. 2014). This special issue addresses the adaptation challenges facing smallholders, ecosystems and ecosystem services in the region. In this introduction, we review the literature on regional climate and its drivers, climate change projections, impacts on agriculture and ecosystems, and information management for adaptation in the region. Short descriptions of the special issue contributions are provided throughout the text.